OsDA1 positively regulates grain width in rice - Cong Li; Jun Liu; Liya Zhang; Tao Li; Hongyu Li; Bin Liu; Tao Zhao (Crop Journal, 2024)
The size and shape of rice grains influence their yield and commercial value. We investigated the role of OsDA1, a rice homolog of the Arabidopsis DA1 gene, in regulating grain size and shape. OsDA1 was highly expressed in young spikelets and glumes. Its overexpression led to enlarged seeds with increased width and decreased length/width ratio (LWR) and knocking out OsDA1 reduced grain width and increased grain length and LWR. A R310K point mutation in the DA1-like domain is a potential target for breeding for increased grain width and length. OsDA1 interacted with TCP gene-family proteins to regulate grain size and shape. Our findings deepen our understanding of the molecular mechanisms underlying grain size regulation and provide useful information for improving grain yield.